Microbiological profile of sputum in stable adult patients with bronchiectasis in the Dnipro region of Ukraine - Gashynova, K. Yu.; Suska, K. S.; Dmytrychenko, V. V. (Medicni Perspektivi, 2020)
Chronic respiratory tract infection and relapsing exacerbations worsen the quality and reduce the life expectancy of patients with bronchiectasis. This work aimed to identify the spectrum of pathogens and to determine their profile of antibiotic resistance in the sputum of patients with bronchiectasis in the Dnipro region. Sputum of 60 patients in a stable phase with confirmed bronchiectasis was a subject to microbiological examination and determination of antibiotic sensitivity according to generally accepted CLSI recommendations. According to the results of the study, it was found that 70% of patients have sputum colonization by pathogens in the stable phase of the disease, and the most common pathogens are Pseudomonas aeruginosa and Haemophilus influenzae, which is in line with the global trend. Haemophilus influenzae was sensitive to ampicillin, amoxicillin, amoxicillin/clavulanate, piperacillin/tazobactam, cefuroxime, ceftriaxone, cefotaxime, cefepime, ciprofloxacin, levofloxacin and moxifloxacin in a hundred percent of cases. However, more than half of the strains of Pseudomonas aeruginosa were resistant to one or more drugs with anti-Pseudomonas activity. In particular, the highest level of resistance was identified to such drugs as imipenem, aztreonam, ceftazidime. The problem of antibiotic resistance is alarming and once again indicates the need for the regular microbiological examination of the sputum of patients with bronchiectasis even in a stable phase for subsequent rational administration of antibacterial therapy.